Fundamental Mechanisms With Reactive Infiltration of Silicon Melt Into Carbon Capillaries. Issue 8 (25th April 2019) - Hofbauer, Peter J.; Rädlein, Edda; Raether, Friedrich
Abstract : The LSI process, that is, the infiltration of molten silicon into porous structures, is one of the most economical techniques for the production of dense C/SiC composites. However, despite decades of development, the phenomena at the infiltration front have not been understood sufficiently. Consequently, a comprehensive model of the reactive infiltration process, which would help to optimize the production process of C/SiC components, has not been established yet. A special thermo‐optical measuring furnace, TOM_ac, enables in situ inspection during liquid silicon infiltration in a controlled atmosphere. Using a novel experimental set‐up, temperatures and atmospheres were varied during silicon melt infiltration into gap capillaries incorporated in glassy carbon. Results clearly demonstrate that the capillary effect is not the rate controlling process as commonly believed but show the importance of gas phase reactions. Besides optical inspection of the infiltration process, quenching experiments combined with SEM analyses of the samples provided a detailed insight into reaction mechanisms and transport processes. Abstract : The rate controlling mechanisms during the reactive infiltration of liquid silicon into carbon preforms are described. Based on in situ measurements at gap capillary samples as well as microstructure investigations on partially infiltrated and quenched samples, it is shown, that gas phase processes control infiltration rate. Additional findings like the temperature and pressure dependence of the infiltration rate are discussed.